PERFORMING DRAMA AS A PROJECT-BASED LEARNING IN ENGLISH LANGUAGE LEARNING CLASSROOM: STUDENTS’ PERCEPTIONS (English Community Journal, 2022)
Project-based learning (PBL) is becoming more and more popular in mainstream education. It is a type of teaching method that allows students to learn something by doing a project devised by the teacher. One project-based learning method used by researchers was through the use of drama. The use of drama in language teaching has long been considered a legitimate practice. According to a recent literature review, English language learners (ELLs) may benefit even more from using drama in the classroom. The purpose of this study was to find out students' perceptions of performing drama as project-based learning in English language learning. This study used descriptive-quantitative method of collecting data through questionnaire. The study found that drama is the best option to facilitate learners' experience of autonomous learning and increase students' opportunities to learn English.